2013
DOI: 10.1007/s00068-013-0302-6
|View full text |Cite
|
Sign up to set email alerts
|

Are soft tissue measurements on lateral cervical spine X-rays reliable in the assessment of traumatic injuries?

Abstract: There is no significant difference between the soft tissue shadows when comparing patients with and without cervical spine fractures on lateral radiographs. Both commonly used measures of soft tissue shadows in clinical practice are insensitive in identifying patients with significant osseous injuries. They, therefore, do not offer any further value in interpreting traumatic cervical spine radiographs. The management of patients with cervical spine trauma in the absence of obvious osseous injury on standard ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…DeBehnke and Havel 22 employed comparable methodology in adults and found similar patterns but did not accept any point on the ROC curve as adequate. Patel et al 16 also demonstrated similar high specificities and low sensitivities in testing adults using the '7 mm at C2 and 2 cm at C7' rule.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…DeBehnke and Havel 22 employed comparable methodology in adults and found similar patterns but did not accept any point on the ROC curve as adequate. Patel et al 16 also demonstrated similar high specificities and low sensitivities in testing adults using the '7 mm at C2 and 2 cm at C7' rule.…”
Section: Discussionmentioning
confidence: 83%
“…1 Although soft tissue swelling on X-ray has been referred to as an aid in identifying injury, 1,2 published measurement methods and recommendations on what constitutes swelling vary, as does the diagnostic significance of said swelling. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Measurements in millimetres (mm) may not be applicable across wide age ranges and an alternative is measurement as a ratio of vertebral body width. Some published normal values are based on primary evidence, but many statements regarding measurement norms are uncited, or citations do not correctly support the measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies performed in adults confirm the above conclusion. 23,[26][27][28] The reported adult sensitivities of PVST range from 5 to 82.5% due to differing methodology: variable PVST dimension standards, cervical spine levels, and combinations of levels measured. 17,23,24,[26][27][28] The standards reported for the upper limits of normal retropharyngeal PVST width in adults vary from 4 to 7 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior-posterior width of PVSTs has long been considered a valuable radiographic measurement for evaluating cervical spine trauma [117], [135]. As the most reliable indicator of this injury, an increase of this shadow or abnormal signal of PVSTs implies the probable oedema or haematoma in the PVSTs (such as the prevertebral fascia, buccopharyngeal fascia, the superior and middle pharyngeal constrictor muscles and the longitudinal esophageal muscle) as well as rupture of anterior longitudinal ligament, secondary to cervical trauma [113], [117], [136].…”
Section: Discussionmentioning
confidence: 99%
“…Specially two radiologists and two orthopedic surgeons jointly measured the prevertebral soft tissues (PVSTs) image according to the 'seven at two and two at seven' rule [113], [114], determined whether the patient had cervical stenosis based on the 'Pavlov ratio' [115], also determined if there was fracture, vertebral hyperosteogenesis or vertebral instability on the X-ray radiographic [116]. The MRI images were used to identify underlying lesions such as rupture of the anterior longitudinal ligament, ligamentum flavum hypertrophy, cervical disc herniation, cervical stenosis, and spinal cord injury [117], [118].…”
Section: Experimental Designsmentioning
confidence: 99%